Pemberdayaan Peran Mahasiswa Menanggapi Perubahan Iklim Melalui Gaya Hidup Berkelanjutan (Sustainable Lifestyle) Peduli Lingkungan - Elisabeth Deta Lustiyati Lustiyati; Nur Alvira Pascawati; Yelli Yani Rusyani; Jati Untari; Ade Puput Melliani; Ade Christian Yanuardo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
The SDGs pay particular attention to climate change. One of them is SDG 13, which aims to take immediate action to combat climate change and its impacts. Higher education is the premier educational institution that plays a vital role in a sustainable future. In order to maintain environmental sustainability, universities dealing with the environment need human resources. Student associations or unions are effective forums for promoting environmental awareness among individual members. This non-profit service aims to provide education on environmentally responsible behavior for sustainable living. The activity was held from 8th to 10th October 2022 at Campus 2 of Respati University Yogyakarta. The participants of this training were members of the student association of Respati University Yogyakarta, and 26 people participated. Educational activities carried out as part of this activity include the presentation of materials on environmental protection, brainstorming on environmental protection actions, focus group discussions on environmental protection work programs, and environmental protection as a form of support for the Green Campus of Respati University Yogyakarta. Contains a statement of protection. The activity was well received by the participants as 12 of the 16 student groups in the study program participated and all participants attended the two-day activity. Students' environmental care behavior is influenced by several indicators. One of them is student involvement in home, college, and character/lifestyle shaping. Universities must play a role in fostering a greener attitude in the academic community through infrastructure, governance, campus activities, research and curricula.